Focus on the Multimodal Role of Biomarkers in Breast Cancer - Lang, Damanpreet K.; Sood, Ankita; Kaur, Rajwinder; Arora, Rashmi; Behl, Tapan (Current Pharmaceutical Design, 2021)
Breast cancer is the most common type of malignancy affecting women worldwide and also stands being the most diagnosed one. Mammography is considered as the golden standard for diagnosis but there are high chances that it can give false- negative as well as false-positive test results. Finding cost-effective, readily available diagnosis along with increased sensitivity as well as specificity is the need right now to decrease the mortality as well as the morbidity rate. The application of biomarkers to clinical use has paved the way for a better prognosis, diagnosis, detection, screening and better clinical results. The efficacy of the treatment is enhanced. Biomarkers are known to cause an advancement in breast cancer study and are expected to improve the quality of life in patients. Not only tissue biomarkers but serum and circulating biomarkers are also of significance in patients. This review highlights the particulars about the current use and application of biomarkers in an effective prognosis, detection, treatment of the breast cancer and also the ones which are currently being studied under clinical trials and have the potential to be advantageous and more specific in the future.
Keywords: biomarkers